Intramural metastasis to the appendix from ascending colon cancer: a case report - Toshiya Abe; Hiroshi Sakai; Masataka Hayashi; So Nakamura; Shin Takasue; Masafumi Sada; Shingo Kozono; Yoshiki Kitaura; Yoshitaka Tanabe; Kazuyoshi Nishihara; Mari Mine; Sadafumi Tamiya; et al. (Surgical Case Reports, 2020)
Abstract Background Intramural metastasis is rare in colorectal cancer, especially metastasis of ascending colon cancer to the appendix. Case presentation A 64-year-old man was admitted to our hospital for surgery for ascending colon cancer detected by medical examination. Colonoscopy identified a type-2 tumor in the ascending colon, which was diagnosed as adenocarcinoma. Abdominal computed tomography revealed focal thickening of the ascending colon and middle of the appendix and swelling of the lymph nodes around the ileocolic artery. The patient underwent laparoscopic right hemi-colectomy with D3 lymph node dissection. Histopathological findings revealed that the ascending colon cancer was moderately differentiated adenocarcinoma with lymphatic and vascular invasion (stage IIIB; pT3N2M0). Additionally, moderately differentiated adenocarcinoma was observed mainly in the submucosa and muscularis propria of the appendix, which was approximately 10 cm proximal to the ascending colon cancer. These findings indicated intramural metastasis to the appendix from the ascending colon cancer. The patient experienced recurrence with lung metastasis 2.5 years after the first surgery. Conclusions Intramural metastasis of ascending colon cancer to the appendix is extremely rare. Because the risk of recurrence and the prognosis for intramural metastasis has not been clarified, careful follow-up is recommended.